Liver transplantation significantly improves global functioning and cerebral processing. Issue 10 (October 2016) - Ahluwalia, Vishwadeep; Wade, James B.; White, Melanie B.; Gilles, HoChong S.; Heuman, Douglas M.; Fuchs, Michael; Gavis, Edith A.; Fagan, Andrew; Tinsley, Felicia; Ganapathy, Dinesh; Thacker, Leroy R.; Sterling, Richard K.; et al.
Abstract : The functional basis of cognitive and quality of life changes after liver transplant is unclear. We aimed to evaluate the neurometabolic and functional brain changes as modulators of cognition and quality of life after transplant in patients with cirrhosis who were with/without pretransplant cognitive impairment and hepatic encephalopathy (HE). Patients with cirrhosis underwent detailed cognitive and quality of life assessment at enrollment and 6 months after transplant. A subset underwent brain magnetic resonance imaging (functional magnetic resonance imaging [fMRI], diffusion tensor imaging [DTI], and magnetic resonance spectroscopy [MRS]) before and after transplant. Changes before and after transplant were analyzed in all patients and by dividing groups in those with/without pretransplant cognitive impairment or with/without pretransplant HE. MRS evaluated ammonia‐related metabolites; fMRI studied brain activation for correct lure inhibition on the inhibitory control test; and DTI studied white matter integrity. Sixty‐six patients (mean Model for End‐Stage Liver Disease score, 21.8; 38 HE patients and 24 cognitively impaired [CI] patients) were enrolled. Quality of life was significantly worse in CI and HE groups before transplant, which improved to a lesser extent in those with prior cognitive impairment. In the entire group after transplant, there was (1) significantly lower brain activation needed for lure inhibition (shown on fMRI); (2) reversal of pretransplant ammonia‐associated changes (shown on MRS); and (3) improved white matter integrity (shown on DTI). Importantly, study findings suggest that pretransplant cognitive impairment serves as a marker for clinical outcomes. Regardless of pretransplant history of HE, it was the pretransplant cognitive impairment that was predictive of both posttransplant cognitive and psychosocial outcomes. Therefore, when working with patients and their families, a clinician may rely on the pretransplant cognitive profile to develop expectations regarding posttransplant neurobehavioral recovery. We conclude that functional brain changes after liver transplant depend on pretransplant cognitive impairment and are ultimately linked with posttransplant cognition and quality of life in cirrhosis. Liver Transplantation 22 1379–1390 2016 AASLD .